A Case Control Study on Physical Activity and Obesity among Adolescent Children in an Urban Area of Tamilnadu - Angeline Grace G; Shanthi Edward; Gopalakrishnan S (Medsci Publications, 2021)
Background: Physical activity has a crucial role in prevention of obesity. Adolescents are required to spend at least 60 minutes a day in physical activity. This Case control study compares physical activity pattern among obese and non-obese adolescent school children studying in an urban area of Tamilnadu. Methods: We recruited 110 age matched obese and non-obese adolescents between the ages of 10-17 years. WHO growth reference charts were used for selecting cases and controls. Data were collected on socio demographic information, physical activity at school and at home, and sedentary behaviour. Results: Inadequate physical activity was noted among 73.6% of cases and 30.9% of controls. Around 83.6% of cases and 68.2% of controls had the regular habit of watching television while having food at home. The factors found to be associated with adolescent obesity were inadequate physical activity (OR: 6.24), sedentary behaviour for more than two hours a day (OR: 4.39) and watching television while having food (OR: 2.39). Conclusion: This study highlights the gross inadequacy of physical activity among obese adolescents. Increased sedentary life style and use of electronic gadgets serve as a risk factor for development of obesity. Public health measures need to be taken to increase the awareness among children and parents on the importance of regular and adequate physical activity. Physical education activities have to be strengthened in schools and students need to be encouraged to involve in diverse physical activities.